Pengaruh Kebutuhan Program Persiapan Pensiun Terhadap Kesiapan Pegawai ASN Dalam Menghadapi Masa Pensiun Pada Dinas Kearsipan Provinsi Sumatera Selatan - Sari, Santika Mayang; Elpanso, Efan (Program Pascasarjana STIE Amkop Makassar, 2023)
In government agencies, most of the human resources are laid off due to retirement. Retirement or retirement is the final stage of serving a State Civil Apparatus (ASN) where at this stage, employees will leave their careers, leaving their attachment to the organization. The purpose of this study is to find out how much influence the needs of the retirement preparation program have on ASN readiness in facing retirement at the Archives Service of South Sumatra Province. The method used in this study is to use quantitative descriptive, and use a Likert scale as a measurement scale, for data analysis using simple linear regression. In this study, to determine the sample, the researcher used a saturated sampling model, namely a sampling technique where all members of the population were used as samples, then the questionnaire was distributed to 50 respondents and the data was processed using SPSS. Based on the results of the study, it shows that the need for a retirement preparation program (X) has a positive and significant effect on retirement readiness (Y). as well as the readiness of employees in facing retirement or the end of their working period. Keywords: Retirement Program Needs; Retirement Readiness.